CFM56- 7B TAKE-OFF ENGINE PERFORMANCE WITH THRUST 26300 LB AND 24200 LB - Joseph Pradana Hutamadi (Vortex, 2021)
As an one of engine manufacturers, CFM produces CFM56-7B with some thrust rating versions to fulfill market demand. In this case, operator has some considerations in choosing engine which is appropriate with the demand. The engine performance is very important to be considered, especially the engine capabilities when it is being maximally operated in takeoff phase.This research discusses about the CFM56-7B engine takeoff performance comparison between 26300 lbs and 24200 lbs thrust rating configuration. By processing Test Cell Result data using formula in Engine Shop Manual - 003, author did a performance calculation to know how much the difference that happened to both of those thrust rating configuration.